1977
DOI: 10.1111/j.1600-0765.1977.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte migration into the healthy dentuious mouth A study in children, adolescents and adults

Abstract: The leukocyte migratory rate (OMR) was estimated with serial mouth rinses, in healthy children, adolesceats and adults with tbe following results (S + s.d.): 0.305 ± 0.094. 0.221 ± 0.102, 0.266 ± 0.115. The number of teeth and the number of erupting teeth did not influence the OMR. The OMR values obtained were uniform with small individual variations, representing healthy conditions in the moutb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
(14 reference statements)
1
14
0
Order By: Relevance
“…The positive relationship observed is likely because increased probing depths lead to increased ulcerated epithelium through which greater numbers of neutrophils migrate in response to the presence of subgingival bacteria. Earlier studies, which utilized time-consuming serial rinses and counting techniques, found similar correlations (12,18). It has been previously shown that the rate at which oral neutrophils migrate into the oral cavity increases in the presence of inflammation (10) and that oral neutrophil counts positively correlate with both increasing pocket depth and the gingival index (11,12).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The positive relationship observed is likely because increased probing depths lead to increased ulcerated epithelium through which greater numbers of neutrophils migrate in response to the presence of subgingival bacteria. Earlier studies, which utilized time-consuming serial rinses and counting techniques, found similar correlations (12,18). It has been previously shown that the rate at which oral neutrophils migrate into the oral cavity increases in the presence of inflammation (10) and that oral neutrophil counts positively correlate with both increasing pocket depth and the gingival index (11,12).…”
Section: Discussionmentioning
confidence: 62%
“…It is important to note that although the control subjects were free from periodontal disease, oral neutrophils were still detected by our oral rinse quantification protocol. This is expected as there is always a bacterial presence in the sulcus, and the constant presence of neutrophils and other mediators of the immune response are important in the maintenance of gingival health (18–20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human mouth has a constant bacterial presence that is kept under control in part by a constant influx of neutrophils from surrounding periodontal tissues. 7 The oral rinse assay enables a noninvasive assessment of neutrophil tissue delivery by measuring the level of neutrophils in oral tissues in patients recovering from HSCT. We outline here the insights gleaned from the noninvasive oral rinse assay used to assess neutrophil recovery in pediatric patients undergoing HSCT.…”
mentioning
confidence: 99%
“…Chronic periodontitis is characterized by increased neutrophil recruitment, gingival inflammation and progressive, irreversible loss of periodontal attachment . In periodontal health, however, neutrophils are constantly being recruited to the oral cavity, without inducing clinically evident inflammation or tissue destruction . Thus, it seems that while the blood neutrophils are naïve, becoming primed or activated only during certain disease states, oral neutrophils in health, which have undergone extravasation and exposure to the oral biofilm are partially activated, and do not cause any overt clinical signs of inflammation.…”
Section: Introductionmentioning
confidence: 99%